Crustal investigations and micro-earthquake survey along Hirapur, Jabaipur, Mandla profile using deep seismic sounding explosion data (MAUSAM, 1990)
The crustal structure around Hirapur, Jabalpur Mandla profile in the Madhya Pradesh region has been studied using the Deep Seismic Sounding (D.S.S.) explO31Ondata. Refraction studies have revealed that there is a two-layer crust. The top layer consists of 23 km of granite and 16 km of blastic layer in the region. Using the velocity model deduced in this work, the hypocentral parameters of micro-earthquakes have been computed. It has been observed that although the seismic activity In the region has been very low during the period of observations and is limited to shadow depth, there IS Indication of a concentration of micro-earthquakes west of Jabalpur, close to Katangl fault which has been found to be deep seated from D.S.S. data.